Platform Shift in Education: Filipino Undergraduate Students’ Attitude towards Speaking English in the Virtual Classroom - Kathleen N. Villanueva (International Journal on Integrated Education, 2022)
The pandemic that halted academic institutions had already initiated a shift to various online learning modalities. With the use of technology and the appropriate applications, virtual classrooms were utilized instead of traditional face-to-face classes. A number of research studies on the shift have also been conducted, yet there is a gap in the speaking English attitude inside virtual classes. Furthermore, students' attitude toward English language learning influence their motivation to become competent, and it is thus stated that the impact on language acquisition is regulated by the students' attitude. Thus, the current study's main goal is to determine Filipino undergraduate students' attitudes toward speaking English in the virtual classroom. The English-Speaking Attitude Questionnaire (ESAQ) of Bui and Intaraprasert (2013) was adapted in this study since it is related to the context of this research. The items in the ESAQ focus on the respondents' attitudes regarding speaking English in the virtual classroom, their motivations for using the language, why it is essential to them, and their perceived English-speaking skills. The data that was collected was from pre-service teachers who are currently having their classes virtually. Moreover, it also explored significant differences in respondents' attitudes towards speaking English across gender and specialization. Results show the overall attitude of the respondents toward speaking English in the virtual classroom was "somewhat positive." On the other hand, there is no significant difference when respondents are grouped according to gender. Finally, specialization was found to have a significant difference in attitude in speaking classes in the virtual classroom. Therefore, despite the paradigm shift in education caused by the pandemic, students' attitudes toward speaking English did not change.